Regulated Efficiency, World Trade Organization Accession, and the Motor Vehicle Sector in China - Joseph F. Francois; Dean Spinanger (Tinbergen Institute, 2004)
This paper is concerned with the interaction of regulated efficiency and World Trade Organization (WTO) accession and its impact on China's motor vehicle sector. The analysis is conducted using a 23 sector–25 region computable general equilibrium model. Regulatory reform and internal restructuring are found to be critical. Restructuring is represented by a cost reduction following from consolidation and rationalization that moves costs toward global norms. Without restructuring, WTO accession means a surge of final imports, though imports of parts could well fall as production moves offshore. However, with restructuring, the final assembly industry can be made competitive by world standards, with a strengthened position for the industry.
Keywords: F13; F14; F17; 330; China Accession to WTO; Automobile Sector; Kraftfahrzeugindustrie; Mitgliedschaft; Internationale Wirtschaftsorganisation; China